Uniting Action Research and Citizen Science: Examining the Opportunities for Mutual Benefit Between Two Movements Through a Woodsmoke Photovoice Study - Evans-Agnew, Robin A.; Eberhardt, Chris (Action Research)
As an emerging movement in participatory inquiry, citizen science presents an opportunity for advancing the disciplinary reach and usefulness of action research. In this article, we explore this opportunity by considering a case study involving youth-driven air sampling, photovoice, and environmental justice in the Pacific Northwest. When combined with photovoice as an action research method, citizen scientists can be empowered through collective learning to transform themselves from data collectors into builders of community knowledge and generators of policy change.
Keywords: Woodsmoke; Air pollution; Air Sampling; Critical Theory; Photovoice; Citizen Science; Adolescent; Youth Action Research; Levoglucosan; Environmental Justice; Pacific Northwest; Asthma